Male Gaze dalam Tari Sekapur Sirih Jambi - Rahmatika Luthfiana Sholikhah; Wening Udasmoro; Rr. Paramitha Dyah Fitriasari (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2020)
Sekapur Sirih Dance is a welcoming dance for important guests in Jambi. This dance must be performed to welcome very important guests at the airport/port. This kind of dance is usually performed by 9 women and 3 men as bodyguards. This is very feminine showing the action of making up performed by the ladies. The article talks about the men’s gaze in the Sekapur Sirih Jambi dance. The male gaze is a theory for dissecting films. The author uses this theory to dissect the performing arts of dance. To see the operation, the male dancers’ gaze can be seen from the stage and also from their movement. This research is qualitative research by conducting literature study, observation, and interview. The results of this study indicate that the operation of the male gaze in a dance performance can be seen from the form of the stage, lighting, and dancer movements.